Pharmacological screening of essential oils for identification of lead compounds to target inflammatory bowel disease - Ferreira, Isabel Cristina do Vale (2011)
Dissertação de mestrado em Biologia Celular e Molecular, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra